The "Escola da Terra" Program in Piauí State: educative experience in the direction of human formation - Luiz Jesus Santos Bonfim; Keylla Rejane Almeida Melo (Universidade Federal do Norte do Tocantins, 2022)
The rural population has historically been excluded from school education, both in its total denial of access as in the quality of training experiences. In the correlation of forces present in the current sociability, the Social Movement for Rural Education has been developing actions that oppose this reality. In the correlation of forces present in the current sociability, the Movement for Rural Education has been developing actions that oppose this reality. The Escola da Terra Program (PET), as one of these actions, has sought to develop continuing education projects for teachers who work in multigrade classes in rural schools, associated with the principles of this movement. The objective of this article is to report educational practices developed in the second edition of the Escola da Terra Program (PET) in the direction of human formation. The study was developed from theoretical research and from the analysis of documents produced in the second edition of PET within the scope of the Federal University of Piauí (UFPI), based in the methodological approach of historical-dialectical materialism. The analysis and reflections reveal that the educational activities carried out within the scope of the formative actions of the Program collaborated in the direction of human formation insofar as they sought to discuss the importance of the articulation of systematized knowledge, reverberated in school contents, articulated to the social practice of the countryside, from the interrelationship of Rural Education principles and historical-critical pedagogy.